Florencio Aburto Trigos. School and university teacher, printer and businessman from Veracruz, 1803-1861 (2023)
Objective: to analyze Florencio Aburto's contributions to elementary education in the state of Veracruz (Mexico) in the first half of the 19th century. Originality/contribution: to address the unknown case of a teacher, who educated his students and renewed teaching methods. His story has gone unnoticed like most stories of education, including teacher biographies. Method: we use concepts of the biographical turn, such as trajectories and cultural maps referring to the chronological contexts and the cultural and geographical spaces of the person being studied. Strategies/Data collection: his contributions to the educational field are recovered from various documentary sources. Some aspects of his personal life and his facets as a printer, bookseller and businessman are also explored. Conclusions: his status as a printer, intellectual and businessman led him to bound with the local power and become a renown teacher of the leading edge. He promoted innovative teaching methods for his time, and following the rhetoric of the authorities, he was also concerned that education should reach all sectors of society, regardless of their social status.